Horrors of the Irish-Union;-Botheration of poor Pat_or_a Whisper across the Channel. - Gillray, James, 1756-1815 (Humphrey, H., 1798)
Scholarly notes may be added at a later date.
1 print : col.
Keywords: Caricatures; Cartoons; Ireland -- History -- Union, 1801; Ireland -- Relations ? Great Britain; Irish -- Caricatures and cartoons